Sintering effects on mechanical properties of composites of bovine hydroxyapatite (BHA) and strontium oxide - (:unkn) unknown (My University, 2008)
The results indicate that 5wt% SrCO3 is useful in producing BHA component with ∼20 MPa compressive strength. However, increase in SrCO3 content decrease the strength.